2015
DOI: 10.1371/journal.pone.0141367
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Chlamydia trachomatis Infections and Preterm Births in a University Hospital in Vitoria, Brazil

Abstract: BackgroundPreterm birth (PTB) is a major determinant of neonatal morbimortality with adverse consequences for health. The causes are multifactorial, with intrauterine infection probably explaining most of these outcomes. It is believed that infection with Chlamydia trachomatis (CT) is also involved in PTB and premature rupture of membranes.ObjetivesTo evaluate the prevalence of and associated factors for CT among cases of PTB attended at a University Hospital in Vitoria, Brazil.MethodsA cross-sectional study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 23 publications
5
10
2
6
Order By: Relevance
“…Results of our study are compatible with those found by Schmidt et al (29) who evaluated the prevalence of and associated factors for CT among cases of PTB attended at a University Hospital in Vitoria, Brazil by cross-sectional study performed among parturient who had preterm birth from June 2012 to August 2013. Odds ratio was used as a measure of association with a 95% confidence interval.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of our study are compatible with those found by Schmidt et al (29) who evaluated the prevalence of and associated factors for CT among cases of PTB attended at a University Hospital in Vitoria, Brazil by cross-sectional study performed among parturient who had preterm birth from June 2012 to August 2013. Odds ratio was used as a measure of association with a 95% confidence interval.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the study conducted by Andrews et al (33) where there were no statistical difference between cases of preterm labor and controls regarding the maternal age and the parity. It is in contrast to the study conducted by Schmidt et al (29) where there were a statistical significant difference between two groups as regard maternal age (p = 0.022).…”
Section: Discussioncontrasting
confidence: 91%
“…Foi encontrada uma alta incidência (18%) da infecção urogenital por C. trachomatis em jovens parturientes de uma maternidade de referência de Belém do Pará, o que representa a maior frequência dessa IST em populações de jovens grávidas do Brasil, pois se manteve superior às prevalências identificadas em outras regiões do país, que variaram de 9,4% a 13,9% 7,8,9,10 . A incidência encontrada também é superior a de outros estudos que investigaram a infecção por C. trachomatis em grávidas de diversas regiões no mundo, mostrando prevalências que variaram de 1,1% a 11,1%…”
Section: Discussionunclassified
“…Neste estudo, foi encontrada a associação significativa da infecção urogenital por C. trachomatis em jovens de idade igual ou inferior a 25 anos, o que é amplamente relatado em várias populações no mundo 10,16,17,18 . Por ser observada ampla exposição aos fatores de risco para as IST nesse período de vida, alguns países desenvolveram os serviços de rastreio no pré-natal, estabelecidos prioritariamente para as mulheres jovens, de até 25 anos de idade 19,20,21,22 .…”
Section: Santos Lm Et Al Alta Incidência Da Infecção Urogenital Porunclassified
See 1 more Smart Citation